Epidemiology and burden of invasive fungal infections in the countries of the Arab League - Joumana Kmeid; Jean-Francois Jabbour; Souha S. Kanj (Elsevier, 2020)
The burden of invasive fungal infections is alarming worldwide. The aim of this paper is to review the published literature and evaluate the knowledge gap pertaining to studies on invasive fungal infections in the countries of the Arab League. Few countries from this region have published reports. The most commonly studied invasive fungal infections is invasive candidiasis. Candida albicans remains overall the most common causative pathogen (33.8-60%), however, non-albicans Candida species are increasing. Antifungal susceptibility testing is non-standardized across the published studies. Data on aspergillosis and other fungal infections is scarce. This sheds light on the need for standardized surveillance in the region encompassing more countries of the Arab League to guide diagnostic approach and empiric therapy.